2001
DOI: 10.1128/jcm.39.7.2717-2718.2001
|View full text |Cite
|
Sign up to set email alerts
|

Pneumocystis carinii Carriage among Cystic Fibrosis Patients, as Detected by Nested PCR

Abstract: A total of 137 sputa from 95 consecutive cystic fibrosis (CF) patients undergoing routine bacteriological surveillance were analyzed for Pneumocystis carinii colonization using nested PCR. Seven of 95 patients (7.4%) were PCR positive, suggesting that P. carinii carriage may exist among CF patients due to their underlying pulmonary disease.Cystic fibrosis (CF) is the most common life-shortening autosomal recessive disorder in Caucasians; it is caused by different mutations in the CF transmembrane conductance r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
36
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 10 publications
3
36
1
Order By: Relevance
“…According to our observations, it is a reliable technique that allowed us to detect Pneumocystis colonization in 12.5% of our patients. This percentage is in agreement with data reported for CF patients from European and Brazilian areas (7.4, 21.5, and 38.2%) (22,24,26) but higher than the value of 1.3% reported by Le Gal et al for a series of 76 CF patients from French Brittany (14). As previously reported (1,17), such geographic differences in Pneumocystis carriage prevalence might be linked with the local Pneumocystis circulation, which may be lower in northern France (14; our results in Lille).…”
supporting
confidence: 82%
See 2 more Smart Citations
“…According to our observations, it is a reliable technique that allowed us to detect Pneumocystis colonization in 12.5% of our patients. This percentage is in agreement with data reported for CF patients from European and Brazilian areas (7.4, 21.5, and 38.2%) (22,24,26) but higher than the value of 1.3% reported by Le Gal et al for a series of 76 CF patients from French Brittany (14). As previously reported (1,17), such geographic differences in Pneumocystis carriage prevalence might be linked with the local Pneumocystis circulation, which may be lower in northern France (14; our results in Lille).…”
supporting
confidence: 82%
“…Despite technical factors that can influence the reported prevalence of Pneumocystis colonization, and according to the abovecited studies (including our results), it appears that CF is associated with lower Pneumocystis colonization rates than are other chronic pulmonary diseases (14,20,22,24,26,27,32). Three studies have reported the association of P. jirovecii and P. aeruginosa in CF patients (14,22,25), but whether Pneumocystis infection/colonization complicated CF-associated lung disease remains unclear.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…The prevalence of colonization varies with the population and the underlying disease. For example, Pneumocystis colonization is detected in individuals with cystic fibrosis, and the prevalence ranges from 1% to 22% (90,253,270). Patients with interstitial lung diseases appear to have a higher prevalence of colonization, especially if they are receiving corticosteroids.…”
Section: Colonization In Animalsmentioning
confidence: 99%
“…Whether a positive result by PCR is indicative of the presence of a clinical disease is controversial [24][25][26][27][28][29][30]. VARGAS et al [31] reported a healthcare worker who was an asymptomatic carrier of PCP after being in contact with a patient confirmed with PCP.…”
Section: Laboratory Diagnosing Techniquesmentioning
confidence: 99%